Dehalogenases for pollutant degradation in brief: A mini review - sefatullah Zakary; Habeebat Adekilekun Oyewusi; Fahrul Huyop (Journal of Tropical Life Science, 2021)
Dehalogenases are microbial enzyme catalysed the cleavage of carbon-halogen bond of halogenated organic compounds. It has potential use in the area of biotechnology such as bioremediation and chemical industry. Halogenated organic compounds can be found in a considerable amount in the environment due to utilization in agriculture and industry, such as pesticides and herbicides. The presence of halogenated compound in the environment have been implicated on the health and natural ecosystem. Microbial dehalogenation is a significant method to tackle this problem. This review intends to briefly describe the microbial dehalogenases in relation to the environment where they are isolated. The basic information about dehalogenases in relation to dehalogenation mechanisms, classification, sources and the transportation of these pollutants into bacterial cytoplasm will be described. We also summarised readily available synthetic halogenated organic compound in the environment.